A Motorcycle Safety System Design based on the Internet of Things - Annisaa Sri Indrawanti; Ridho Rahman Hariadi; Eka Prakarsa Mandyartha; Agung Mulyono (Jurnal Teknologi dan Manajemen, 2024)
A huge number of motorbike thefts are still happening in Surabaya City. The most way the thief does to steal the motorbike is damaging the ignition lock using a "T key" so that the motorbike can be started and can be taken easily by thief. Besides that, there are still many other ways to thief the motorbike. The number of theft cases indicates that there are some weaknesses in the safety system on motorbikes made by manufacturers, especially on motorbikes that use the conventional ignition lock system. Along with the rapid development of increasingly sophisticated technology, it can be utilized to improve the security system on motorbikes. The conventional ignition lock is very easy to break into and is not effective in preventing theft. Designing a system that can turn on a motorcycle through an e-KTP scanning using RFID can be the respond to the huge number of theft cases in Surabaya City. This system uses NodeMCU ESP8266 as a microcontroller that is connected to modules such as RFID, GPS, and relays. Through this system, the owner can also monitor the position of his motorcycle through an application connected to the GPS and microcontroller placed in the motorcycle. In case of theft, the motorcycle owner can turn off the motorcycle through the application then the motorcycle will die and cannot be restarted.